2022
DOI: 10.3390/f13091340
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Collective Forestland Tenure Reform on Rural Household Income: The Background of Rural Households’ Divergence

Abstract: As the direct subject of collective forestland tenure reform, increasing farmers’ income is an important goal of collective forestland tenure reform and the key to sustainable management of forest resources. Based on the survey data of 1276 rural households in 18 counties in 9 provinces, we construct a theoretical analysis framework of the impact of collective forestland tenure reform on household income from the perspective of rural household differentiation and elucidate the mechanism of the effect of collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In other scholars' studies, it was found that, in terms of geographical location conditions, the more developed areas in east-central China, areas with good forestry resource endowment, and areas with significant reform are relatively more efficient in developing forestry and more effective in largescale operation [23], and academic research hotspots are also focused on relevant regions with more diversified business models and relatively obvious farmers' willingness to engage in forest management, as concluded by Han [73], Zheng [24], and Hu [74] in related studies; however, in this study, it is found that the factors of scale operation and diversification have no effect on the willingness of minority farmers to engage in forest management.…”
Section: Impact Of Policy Guidance On Willingness To Engage In Forest...mentioning
confidence: 95%
See 1 more Smart Citation
“…In other scholars' studies, it was found that, in terms of geographical location conditions, the more developed areas in east-central China, areas with good forestry resource endowment, and areas with significant reform are relatively more efficient in developing forestry and more effective in largescale operation [23], and academic research hotspots are also focused on relevant regions with more diversified business models and relatively obvious farmers' willingness to engage in forest management, as concluded by Han [73], Zheng [24], and Hu [74] in related studies; however, in this study, it is found that the factors of scale operation and diversification have no effect on the willingness of minority farmers to engage in forest management.…”
Section: Impact Of Policy Guidance On Willingness To Engage In Forest...mentioning
confidence: 95%
“…The transfer of collective forest rights has been steadily promoted, and the number of new business entities reached 294,300, operating more than 280 million mu of forest land. In recent years, although the reform of collective forest rights system has achieved good results, the productivity of collective forest land has not yet been fully released, the comprehensive benefits and operational efficiency of collective forestry [22] are still not high, the economic income from forestry for forest landowners is relatively small [23].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Control variables. Considering that farmers' forestry income is also influenced by other factors besides the forestry industry, and addressing the endogeneity problem caused by omitted variables, we selected a series of control variables based on relevant studies and the principles of availability, comparability, and quantifiability (Abdulai et al, 2016;Abhilash, 2018;Li et al, 2021a;Lin & Chen, 2020;Lu et al, 2018;Lu et al, 2020;Wei et al, 2022;Xiong et al, 2018;. Control variables refer to potential factors or conditions other than experimental variables in an experiment that affect the changes and results of the experiment.…”
Section: Variable Selectionmentioning
confidence: 99%
“…②Rural human capital level (X3). Rural human capital, as an important input factor in forestry production and operation, has a significant promoting effect on the growth of farmers' forestry income (Wei et al, 2022). The per capita education years of rural residents are used to measure the level of rural human capital.…”
Section: Variable Selectionmentioning
confidence: 99%
“…Liu et al (2017b) demonstrated through survey data that the CFTR significantly increased both forestry income and total income for households [21]. However, Wei Jian et al (2022) found in their study that the effect of the CFTR on increasing income varied significantly among households of different income levels, with a greater increase in income for wealthier households than for poorer ones [22]. Zang et al (2015) showed that the CFTR gradually increased the income gap between households [23].…”
Section: Introductionmentioning
confidence: 99%